Enhancing cold atmospheric plasma treatment of cancer cells by static magnetic field. Issue 1 (17th October 2016) - Cheng, Xiaoqian; Rajjoub, Kenan; Shashurin, Alexey; Yan, Dayun; Sherman, Jonathan H.; Bian, Ka; Murad, Ferid; Keidar, Michael
Abstract : It has been reported since late 1970 that magnetic field interacts strongly with biological systems. Cold atmospheric plasma (CAP) has also been widely studied over the past few decades in physics, biology, and medicine. In this study, we propose a novel idea to combine static magnetic field (SMF) with CAP as a tool for cancer therapy. Breast cancer cells and wild type fibroblasts were cultured in 96‐well plates and treated by CAP with or without SMF. Breast cancer cells MDA‐MB‐231 showed a significant decrease in viability after direct plasma treatment with SMF (compared to only plasma treatment). In addition, cancer cells treated by the CAP‐SMF‐activated medium (indirect treatment) also showed viability decrease but was slightly weaker than the direct plasma‐SMF treatment. By integrating the use of SMF and CAP, we were able to discover their advantages that have yet to be utilized. Bioelectromagnetics. 38:53–62, 2017. © 2016 Wiley Periodicals, Inc.